2021
DOI: 10.1016/j.aninu.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Arginine metabolism and its functions in growth, nutrient utilization, and immunonutrition of fish

Abstract: Fish have limited ability in endogenous biosynthesis of arginine. Arginine is an indispensable amino acid for fish, and the arginine requirement varies with fish species and fish size. Recent studies on fish have demonstrated that arginine influences nutrient metabolism, stimulates insulin release, is involved in nonspecific immune responses and antioxidant responses, and elevates disease resistance. Specifically, arginine can regulate energy homeostasis via modulating the adenosine 5'-monophosphate (AMP)-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 137 publications
(191 reference statements)
0
13
0
Order By: Relevance
“…pathways play important roles in regulating normal physiological functions and promoting growth and development of the body (Newsholme et al, 2003;Wang, Li, et al, 2021;Wang, Xu, & Ai, 2021).…”
Section: Ta B L E 3 Statistical Results Of Protein Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…pathways play important roles in regulating normal physiological functions and promoting growth and development of the body (Newsholme et al, 2003;Wang, Li, et al, 2021;Wang, Xu, & Ai, 2021).…”
Section: Ta B L E 3 Statistical Results Of Protein Identificationmentioning
confidence: 99%
“…We also identified growth metabolism‐related pathways from KEGG analysis, including organic selenium compound metabolism (ko00450), alanine, aspartate, and glutamate metabolism (ko00250), arginine biosynthesis (ko00220) and arginine and proline metabolism (ko00330). The glutamine and glutamate metabolism (ko00471) pathways play important roles in regulating normal physiological functions and promoting growth and development of the body (Newsholme et al, 2003; Wang, Li, et al, 2021; Wang, Xu, & Ai, 2021). Studies have shown that selenium is an essential micronutrient to improve the growth and health of animals, and plays an important role in the anti‐oxidation, immunity and detoxification of aquatic organisms (Khan et al, 2016; Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Te reasons for the signifcant variation may be due to diferent species, growth stages, dietary protein sources and contents, composition of dietary protein, amino acids, water temperature, salinity, and/or experimental assessment indices [16]. In addition, carnivorous species have higher dietary arginine requirements than omnivorous fsh [17]. M. albus is a carnivorous fsh; thus, higher dietary arginine requirements are reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that dietary supplementation creatine improved L. vannamei flesh quality cultured in freshwater ( 5 ). Creatine is an essential metabolite of arginine ( 29 ). However, our study found that the creatine content of hepatopancreas and muscle was not affected by adding dietary arginine.…”
Section: Discussionmentioning
confidence: 99%